2004
DOI: 10.1038/sj.ijo.0802861
|View full text |Cite
|
Sign up to set email alerts
|

Substrate cycling between de novo lipogenesis and lipid oxidation: a thermogenic mechanism against skeletal muscle lipotoxicity and glucolipotoxicity

Abstract: Life is a combustion, but how the major fuel substrates that sustain human life compete and interact with each other for combustion has been at the epicenter of research into the pathogenesis of insulin resistance ever since Randle proposed a 'glucose-fatty acid cycle' in 1963. Since then, several features of a mutual interaction that is characterized by both reciprocality and dependency between glucose and lipid metabolism have been unravelled, namely:(i) the inhibitory effects of elevated concentrations of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 78 publications
4
65
0
1
Order By: Relevance
“…7,49 It is, however, not the aim of this paper to cover extensively EE regulatory systems, and readers can refer to several papers that have been written on the topic. 5,42,[48][49][50][51][52][53][54][55] Similarly, cellular mechanisms on the basis of human body thermogenesis, such as mitochondrial adenosine triphosphate synthesis efficiency, 56,57 uncoupling proteins 53,58 and their related increased muscle efficiency 59 will not be covered in this paper, as they have been directly addressed in their respective cited references. This conceptual paper will rather describe three conditions that have been associated to adaptive thermogenesis and that may thus represent limiting factors in weight loss, and confer a significant susceptibility to weight gain/regain in some individuals: body weight loss and regain cycles, organochlorine plasma concentration and hypoxia in severe form of obstructive sleep apnea.…”
Section: Determinant Factors Associated With the Adaptive Thermogenesismentioning
confidence: 99%
“…7,49 It is, however, not the aim of this paper to cover extensively EE regulatory systems, and readers can refer to several papers that have been written on the topic. 5,42,[48][49][50][51][52][53][54][55] Similarly, cellular mechanisms on the basis of human body thermogenesis, such as mitochondrial adenosine triphosphate synthesis efficiency, 56,57 uncoupling proteins 53,58 and their related increased muscle efficiency 59 will not be covered in this paper, as they have been directly addressed in their respective cited references. This conceptual paper will rather describe three conditions that have been associated to adaptive thermogenesis and that may thus represent limiting factors in weight loss, and confer a significant susceptibility to weight gain/regain in some individuals: body weight loss and regain cycles, organochlorine plasma concentration and hypoxia in severe form of obstructive sleep apnea.…”
Section: Determinant Factors Associated With the Adaptive Thermogenesismentioning
confidence: 99%
“…urocortins). 93,94,98 These hormones can interact to stimulate thermogenesis via the enhancement of AMPK and PI3K signaling either by acting directly on skeletal muscle, or centrally through the sympathetic-thyroid axis via norepinephrine (NE) and triiodothyronine (T3). By interfering with PI3K and/or AMPK signaling in skeletal muscle, the actions of the adipose-specific signal(s) that sense the state of depletion (or delayed expansion) of the adipose tissue fat stores will suppress skeletal muscle thermogenesis, which during refeeding will lead to concomitant insulin and leptin resistance.…”
Section: Muscle-adipose Glucose Redistributionmentioning
confidence: 99%
“…They concluded that because this reaction occurred with ezetimibe monotherapy and was accompanied with other signs of impaired fatty acid oxidation, the toxicity may not be related to a pharmacokinetic interaction but to impaired fatty acids oxidation. Indeed, the concept of lipotoxicity is of importance and is evolving in the literature (17).…”
Section: Discussionmentioning
confidence: 99%